2011
DOI: 10.1039/c1dt10960j
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigating 2,5-di(pyridin-2-yl)pyrazine ruthenium complexes: selective deuteration and Raman spectroscopy as tools to probe ground and excited-state electronic structure in homo- and heterobimetallic complexes

Abstract: The mono- (1) and dinuclear (2) ruthenium(II) bis(2,2'-bipyridine) complexes of 2,5-di(pyridin-2-yl)pyrazine (2,5-dpp), for which the UV/Vis absorption and emission as well as electrochemical properties have been described earlier, are reinvestigated here by resonance, surface enhanced and transient resonance Raman spectroscopy together with selective deuteration to determine the location of the lowest lying excited metal to ligand charge transfer ((3)MLCT) states. The ground state absorption spectrum of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Similar to natural photosynthesis, also in various artificial heteroleptic metal-complex-based systems a wavelength dependence of the initial excited-state localization on specific oligopyridine ligands has been reported. As, for example, exemplified for the heterodinuclear hydrogen-evolving catalyst [(tbbpy) 2 Ru­(tpphz)­PdCl 2 ]­(PF 6 ) 2 (tbbpy = 4,4′- tert -butyl-2,2′-bipyridine and tpphz = tetrapyridophenazine; Figure , complex 1 ), localization of the electron density in the initially populated excited state and subsequent relaxation pathways additionally determine the photocatalytic efficiency of the system …”
Section: Introductionmentioning
confidence: 83%
“…Similar to natural photosynthesis, also in various artificial heteroleptic metal-complex-based systems a wavelength dependence of the initial excited-state localization on specific oligopyridine ligands has been reported. As, for example, exemplified for the heterodinuclear hydrogen-evolving catalyst [(tbbpy) 2 Ru­(tpphz)­PdCl 2 ]­(PF 6 ) 2 (tbbpy = 4,4′- tert -butyl-2,2′-bipyridine and tpphz = tetrapyridophenazine; Figure , complex 1 ), localization of the electron density in the initially populated excited state and subsequent relaxation pathways additionally determine the photocatalytic efficiency of the system …”
Section: Introductionmentioning
confidence: 83%
“…Ligand deuteration has also been shown to influence the excited-state properties of complexes. , Ligand deuteration modifies the stretching frequency and amplitude associated with the nonradiative deactivation ( k nr ) modes of the excited states of inorganic complexes. In deuterated species, nonradiative deactivation is decreased due to the increased mass of deuterium dampening the nonradiative deactivation modes associated with C–D bonds compared to equivalent C–H bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Structural assignment of mono- and multimetallic complexes containing bidentate polypyridyl ligands using 1 H NMR spectroscopy is difficult given the large number of nearly equivalent aromatic protons, the number of structural isomers and low symmetry of the complexes. Deuteration of select terminal ligands (TL) or BL permits assignment of the 1 H NMR spectrum of nondeuterated ligands within the supramolecular assembly. This was demonstrated with the complex [(bpy) 2 Ru­(L)] 2+ (L = 5,6,10,11-tetrahydro-16,18-diazadipyrido­[2,3- a :3′,2′- n ]­pentacene). , Substitution of bpy with d 8 -bpy reduces the number of nonequivalent aromatic proton signals associated with bpy and L from 26 to 10, leaving proton signals unique to L. This clarifies the 1 H NMR spectrum and allows for full assignment of previously indistinguishable signals from L. , Simplification of the 1 H NMR using deuterated TLs or BLs allows for enhanced structural characterization while also offering a method to study H 2 O reducing photocatalysts during reduction or photocatalysis to gain insight into the photocatalytic functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that the 2,5-dpp bridge enables relatively strong coupling between the metal centres and that the emissive state for the [(bpy) 2 Ru-(2,5-dpp)] 2+ and [(bpy) 2 Ru-(2,5-dpp)-Ru(bpy) 2 ] 4+ compounds is dpp-based. 15- 23 Absorption spectroscopy shows that RuPd and EtOOC-RuPd have similar features with the intraligand and metal-to-bpy charge transfer bands being shifted towards lower energy by ca. 15-40 nm.…”
mentioning
confidence: 99%